The Influence of Politeness Norms and Language Skills on How Students Communicate with Teachers in Civic Education Learning Subjects - Sari, Juliana; Rejeki, Sri; Saddam, Saddam (Edunesia : Jurnal Ilmiah Pendidikan, 2025)
This study investigates the influence of politeness norms and language skills on communication procedures between students and teachers in junior and senior high school students learning subjects in pink. This research method uses quantitative research with an observational approach involving 92 respondents, and this research instrument uses a Likert scale with 92 questions. The data results using multiple regression tests show that the influence of politeness norms on communication manners significantly affects communication manners with a regression value of 18.6%. Annova F produces a value of 10,024, indicating the significance of the model as a whole, while the sign value of 0.000 confirms each independent variable. This study plays an important role in understanding the influence of politeness norms and language skills on communication manners between students and teachers in civic education learning subjects. This research provides insight into how politeness norms and language skills affect communication between students and teachers, especially in Civics subjects at the junior and senior high school levels.